2013
DOI: 10.1136/tobaccocontrol-2012-050939
|View full text |Cite
|
Sign up to set email alerts
|

Tax, price and cigarette brand preferences: a longitudinal study of adult smokers from the ITC Mexico Survey

Abstract: Background Recent tax increases in Mexico differed in structure and provide an opportunity to better understand tobacco industry pricing strategies, as well as smokers’ responses to any resulting price changes. Objectives To assess if taxes were passed onto consumers of different cigarette brands, the extent of brand switching, and predictors of preference for cheaper national brands. Methods Using data from three waves of the Mexican administration of the ITC Survey, we analyzed self-reported brand and pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
30
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 36 publications
(37 citation statements)
references
References 17 publications
1
30
0
Order By: Relevance
“…The survey included participants living in 150 census tracts, with an average of 15 participants per census tract in 2012 (range [4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22].…”
Section: Study Samplementioning
confidence: 99%
See 1 more Smart Citation
“…The survey included participants living in 150 census tracts, with an average of 15 participants per census tract in 2012 (range [4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22].…”
Section: Study Samplementioning
confidence: 99%
“…10 Data from the Mexican administration of the International Tobacco Control Policy Evaluation Survey (ITC) showed that, despite the long-standing ban on single cigarettes, in 2006, 9.1% of adult smokers bought singles at their last cigarette purchase. 11 There are several potential explanations for the continued prevalence of singles. First, selling singles can be highly profitable for tobacco vendors; single cigarettes are generally sold for more than twice the per-unit price of packaged cigarettes.…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, extensive evidence has indicated that many smokers, in particular confirmed smokers, engage in tax avoidance or evasion by switching to cheaper cigarette brands as taxes and prices increase,11–20 and reducing price gaps may incentivise smokers to trade up to higher-priced cigarettes of better quality 20 21. In addition, a handful of studies show that smokers may also switch to cheaper tobacco products (eg, roll-your-own, RYO) or different tobacco products (eg, smokeless tobacco) in response to a change in the relative price or tax 22–26.…”
Section: Introductionmentioning
confidence: 99%
“…It is possible that national cigarette production in Mexico may be considerably different from the international and U.S. brands, and purchasing of these brands may also differ within Mexico. 62 Therefore, when making comparisons across countries, we cannot conclude if women in our study are being exposed to the same cigarette smoking exposures, that is, types of chemicals used in cigarette production. These factors pertaining to cigarette types and brands should be considered with future international studies of smoking and breast cancer.…”
Section: Discussionmentioning
confidence: 93%